Penentuan Klasifikasi Tingkat Stadium Demam Berdarah Dengue (Dbd) Berdasarkan Jumlah Sel Darah Putih Berbasis Image Processing - Amelia Yolanda -; Rahmadi Kurnia - (Jurnal Ilmiah Poli Rekayasa, 2015)
In medicine, knowing the number of blood cells is very important because many diseases are caused by a number of blood cells that are outside the normal condition. Blood cells can be calculated in the conventional way, but if the blood cells are counted quite a lot of takes up a lot and the results may be less accurate. In this study the authors will try to count the number of normal white blood cells to determine the level of classification stage of dengue fever based on the number of white blood cells. This research applies some processes to be able to identify objects forming white blood cells which are leukocytes and platelets. Different template image and different processes are required in order to detect the position and the calculation of the number of objects in an image. Reverse image is in the process of look up table method to detect leukocytes, while the color conversion is a process that is applied to detect platelets.